PENINGKATAN HASIL BELAJAR SISWA PADA TEKS CERITA FANTASI MELALUI DISCOVERY LEARNING DAN PEMBELAJARAN BERDIFERENSIASI BERBASIS YOUTUBE - Lisa Ariyani; Rini Utami, Sintowati; Lestari, Lita (Satya Widya, 2025)
Indonesian language learning has a strategy to improve literacy in students, especially in the aspects of reading and writing text types, one of which is through fantasy story texts. However, the results of initial observations showed that seventh grade students of SMP Labschool Jakarta still had difficulty in understanding the structure and linguistic characteristics of fantasy story texts, with an average initial score of only 53 and a completion rate of 15%. This study aims to improve learning outcomes in fantasy story texts through the application of the discovery learning model in a differentiated learning approach assisted by YouTube media. This study used the Classroom Action Research (CAR) method which was implemented in three cycles, with the stages of planning, implementation, observation, and reflection. The results showed a significant increase in student learning outcomes, with the average score increasing from 53 in the pre-cycle to 78 in cycle II, and reaching 91 in cycle III, and learning completion increasing from 15% to 79%. These findings indicate that the application of discovery learning through differentiated learning based on YouTube media is effective in improving student learning outcomes, activeness, and motivation in fantasy story text material. This model is also able to facilitate the diversity of students' learning readiness, creating an inclusive, adaptive, and student-centered learning process.